Identification of Biologically Active Ganoderma lucidum Compounds and Synthesis of Improved Derivatives That Confer Anti-cancer Activities in vitro - Martínez-Montemayor, Michelle M.; Ling, Taotao; Suárez-Arroyo, Ivette J.; Ortiz-Soto, Gabriela; Santiago-Negrón, Camille L.; Lacourt-Ventura, Mercedes Y.; Valentín-Acevedo, Anibal; Lang, Walter H.; Rivas, Fatima (Frontiers in Pharmacology, 2019)
We previously reported that Ganoderma lucidum extract (GLE) demonstrate significant anticancer activity against triple negative inflammatory breast cancer models. Herein, we aimed to elucidate the bioactive compounds of GLE responsible for this anticancer activity. We performed NMR, X-ray crystallography and analogue derivatization as well as anti-cancer activity studies to elucidate and test the compounds. We report the structures of the seven most abundant GLE compounds and their selective efficacy against triple negative (TNBC) and inflammatory breast cancers (IBC) and other human cancer cell types (solid and blood malignancies) to illustrate their potential as anticancer agents. Three of the seven compounds (ergosterol, 5,6-dehydroergosterol and ergosterol peroxide) exhibited significant in vitro anticancer activities, while we report for the first time the structure elucidation of 5,6-dehydroergosterol from Ganoderma lucidum. We also show for the first time in TNBC/IBC cells that ergosterol peroxide (EP) displays anti-proliferative effects through G1 phase cell cycle arrest, apoptosis induction via caspase 3/7 activation, and PARP cleavage. EP decreased migratory and invasive effects of cancer cells while inhibiting the expression of total AKT1, AKT2, BCL-XL, Cyclin D1 and c-Myc in the tested IBC cells. Our investigation also indicates that these compounds induce reactive oxygen species, compromising cell fate. Furthermore, we generated a superior derivative, ergosterol peroxide sulfonamide, with improved potency in IBC cells and ample therapeutic index (TI>10) compared to normal cells. The combined studies indicate that EP from Ganoderma lucidum extract is a promising molecular scaffold for further exploration as an anti-cancer agent.